Advancing teacher professional development for interactive learning technologies in digitally enriched classrooms - Parta, Ida Bagus Made Wisnu; Soelistya, Djoko; Hanafiah, Hanafiah; Basri, Teuku Hasan; Saputri, Dwi Yuniasih (Journal of Educational Management and Instruction (JEMIN), 2025)
The rapid evolution of digital technologies has redefined educational practices and emphasized the need to enhance teachers’ competencies in implementing interactive learning tools. This study aims to examine the challenges and opportunities associated with teacher professional development in digitally enriched classrooms. Adopting a qualitative case study design, the research utilizes semi-structured interviews, classroom observations, and document analysis to investigate how targeted professional development programs influence pedagogical practices and support the integration of interactive technologies. A total of 25 teachers were selected from a diverse mix of educational levels, including primary, secondary, and tertiary institutions. Findings indicate that structured training programs, grounded in theoretical frameworks such as TPACK and SAMR, significantly enhance teachers’ capacity to foster student engagement and improve learning outcomes. Additionally, the study underscores the importance of collaborative learning communities and sustained support systems in maintaining teachers’ digital competence. This study concludes that continuous, theory-informed, and context-sensitive professional development initiatives are essential for equipping educators to navigate the complexities of modern digital classrooms. This study contributes to the growing literature on digital pedagogy by providing practical insights and strategic recommendations for advancing teacher development in the context of interactive learning technologies.